Security enhancement of the communication-efficient AUTHMAC_DH protocols - Lv, Chao (2013)
Authentication and key distribution (AKD) protocols have become more important in the design of communication systems. The design criteria of the AKD protocols include the scalability, the communication efficiency, the computational efficiency, and the robustness of security. In this paper, we first analyze the vulnerability of an AKD protocol under the off-line guessing attack. Then, we propose an enhanced AKD protocol to overcome the vulnerability. Security analysis and formal verification by using AVISPA toolkit show that the proposed protocol can keep all the previous properties and is secure against the off-line guessing attack.